Patient safety : a case-based comprehensive guide - Agrawal, Abha (Springer New York, 2014)
Despite the evolution and growing awareness of patient safety, many medical professionals are not a part of this important conversation.  Clinicians often believe they are too busy taking care of patients to adopt and implement patient safety initiatives and that acknowledging medical errors is an affront to their skills. Patient Safety provides clinicians with a better understanding of the prevalence, causes and solutions for medical errors; bringing best practice principles to the bedside.  Written by experts from a variety of backgrounds, each chapter features an analysis of clinical cases based on the Root Cause Analysis (RCA) methodology, along with case-based discussions on various patient safety topics.  The systems and processes outlined in the book are general and broadly applicable to institutions of all sizes and structures.  The core ethic of medical professionals is to "do no harm".  Patient Safety is a comprehensive resource for physicians, nurses and students, as well as healthcare leaders and administrators for identifying, solving and preventing medical error.